A novel high-toughness, organic/inorganic double-network fire-retardant gel for coal-seam with high ground temperature. (1st March 2020) - Li, Yongsheng; Hu, Xiangming; Cheng, Weimin; Shao, Zhiang; Xue, Di; Zhao, Yanyun; Lu, Wei
Graphical abstract: Highlights: High-toughness P(AA-co-AM)/WG gel was prepared by free radical polymerization. P(AA-co-AM)/WG gel is fit for coal-seam condition with high ground temperature. P(AA-co-AM)/WG gel has advantages of plugging, resisting, and cooling. P (AA-co-AM)/WG gel's formation, inhibition, and fire prevention mechanism is discussed. Abstract: In order to address the issue of spontaneous combustion of coal, this paper proposes a high-toughness hydrogel (P(AA-co-AM)/WG gel) for fire prevention and extinction, which is suitable for the conditions of coal-seam with high ground temperatures. In the initial stage, the silicic acid molecules in the material system react under the action of the coagulant to form the first network structure. Simultaneously, the superabsorbent monomers in the material system use the geothermal energy in the mines to polymerize and form the second network structure. The first and second network cross each other, forming P(AA-co-AM)/WG gel with interpenetrating network structure and high toughness. The differences in WG gel, P(AA-co-AM), and P(AA-co-AM)/WG gels were analyzed via testing of their in-situ infrared, and viscoelasticity. The results indicate that P(AA-co-AM)/WG gel had the best water retention, elasticity, inhibitory performance, compression resistance and lowest cost among the studied gels. In addition, the fire extinction experiments of comparison with other fire extinction materials indicated that P(AA-co-AM)/WG gel could uniformly cover the surface of the burning coal body forming a dense enwrapping on the coal and densely filling the cracks. Moreover, the fire extinction effect of the proposed gel is stable as there was no re-ignition phenomenon.